UNTILIZATION OF POCKET BOOKS AS PREMENOPAUSAL MOTHER'S EDUCATION ON ANXIETY FACING MENOPAUSE - Utami, Intan Tri; Sumasto, Hery; Jeniawaty, Sherly; Harumi, Ani Media (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
The first phase of a woman's natural experience before menopause is called premenopause.Decreased estrogen levels affect the physical and psychological changes of menopausal women, and trigger anxiety. This study uses the pre-experiment method through the one group pretest-posttest designs approach. The sample was taken by purposive sampling with a total of 33 respondents. The independent variables of this study were pocket book education, the dependent variables of knowledge and anxiety. Data collection used a knowledge questionnaire and a zung self-rating anxiety scale (ZSAS). To analyze whether there is an effect, a test with a wilcoxon signed rank test with a p value of <0.05 is used.The results of the study were found to increase knowledge and reduce the level of anxiety of premenopausal mothers after education using pocket books. After the test was carried out, the results of the influence of pocket book education on knowledge and anxiety facing menopause with a p value of 0.000 < α 0.05 were obtained. It can be concluded that there is an influence of pocket book education on premenopausal knowledge and anxiety facing menopause. So it is recommended that premenopausal mothers make the best use of insights about menopause.